Modeling of research competence formation system of the future software-engineers - Вінник, Максим Олександрович (ScienceRise: Pedagogical Education, 2016)
In the article it was theoretically analyzed the system of training of the future software engineers in HEI educational environment and presented the model of formation of research competence of the future software engineers in the conditions of HEI educational environment. The grounding of effective conditions of formation of the research competence of the future software engineers in the conditions of HEI educational environment provides the elaboration of theoretical model of this process. The structural-functional model of formation of the research competence of future software engineers is oriented on the development of motivation-value, cognitive and activity components of research competence of future software engineers at realization of correspondent pedagogical conditions, use of information technologies, organization of step-by-step involvement of students to the research activity, systematic monitoring of mastering the research competence by students. In formation of research competence the important role is given to the specially organized means of training students for research activity. Among the means of formation of research competence besides the traditional ones (verbal means, textbooks, schoolbooks; visual means; models) the most effective are ICT means. The constructed model of formation of research competence of future software engineers has a system character that is provided by interconnection and mutual conditionality of its components. Theoretically grounded structural-functional model of formation of research competence of the future software engineers gives a possibility to understand the character of mutual dependence between the structural components of the process of formation of research components in students, synthesize and reveal the typical features of this process, to make correction of the separate elements if it is necessary for the optimal attainment of the set aim